IoT Design for Disaster Mitigation and Energy Efficiency in the Kaliandra Program: Desain IoT untuk Mitigasi Bencana dan Efisiensi Energi di Program Kaliandra - Abu Yazid Bustomi; Muhammad Zayyan Abiyyusa Firdaus; Denny Saputra Ramadhan (ANDIL Mulawarman Journal of Community Engagement, 2026)
The slope stability of the Kaliandra Program infrastructure is vulnerable to hydrological risks and energy inefficiencies caused by manual irrigation mechanisms that rely on human intervention. This community service activity designed a distributed automatic control system to overcome these issues. The core novelty of this intervention lies in the synergistic integration of a circular economy, localized edge computing, and preventive disaster mitigation. By repurposing discarded electronic set-top boxes into autonomous local cloud servers, the system effectively severs dependence on vulnerable public internet infrastructure. A distributed control architecture was developed utilizing the system development life cycle methodology. Empirical evaluations confirm that the wireless mesh topology guarantees robust data transmission across severe non-line-of-sight topographies, sustaining a perfect packet delivery ratio of 100 percent and a 210-millisecond latency despite a degraded signal strength of -81.33 decibel-milliwatts. Furthermore, the implementation of automated short-duration pulse drip irrigation mitigates critical soil saturation while yielding a verified net energy saving of 6.31 kilowatt-hours monthly. At a highly efficient capital expenditure of 4,919,650 Rupiah, the integration of software-defined protection and touchless interfaces eradicates electrical shock hazards for local facility operators.